Analisis Hasil Belajar Mahasiswa Menggunakan Media Cetak dengan Media Elektronik Pada Mata Kuliah Matematika Ekonomi di Universitas PGRI - Widalismana, Merlyn; Lestari, Neta Dian (Universitas Nusantara PGRI Kediri, 2017)
Electronic media and print media is one of the media that began to be used in teaching and learning at the University. Variable in this research Electronic media as independent variable 1 or X1 and Print media as independent variable 2 or X2. Samples were taken by random sampling that is class 3A and class 3B from population of 2 class. The methods used are comparative expri- sive and descriptive. Data analysis technique use t test equation with 95% confidence level (α 0.05). Based on the results of the discussion can be concluded that the liveliness of students who learn to use electronic media average 17.54 while those who learn using print media 78.20. And based on the tests conducted it is known that the average student's learning grade electronic media 77.42 while those who learn to use print media 83.72. Proof of hypothesis shows thitung = 8,524> ttabel = 8,283 means accept Ha, which means there are differences in student learning outcomes in the subjects of Economic Mathematics using print media with electronic media at the University of PGRI Palembang Lesson Year 2016/2017. From this result suggested to lecturer in Economic Mathematics subject to Print media can be used as an alternative learning method, especially to improve student activeness in learning lecturer to support the improvement of student learning result.